Behavior of mortars with different types of cement when induced to Delayed Ettringite Formation (DEF) - Tiecher, Friancieli; Langoski, Marinés; Hasparyk, Nicole (Revista ALCONPAT, 2021)
The purpose of this paper is to present an evaluation of different types of cement and the incidence of Delayed Ettringite Formation (DEF) through mortar composites cast in the laboratory and exposed to a high curing temperature over a 12-month study period. DEF represents one of the types of Internal Sulfate Attacks (ISA) related to an expansive chemical reaction that occurs inside of concrete involving the sulfates from cement. Experiments involved the assessment of expansions, compressive and tensile strengths as well as microstructural characteristics over time. It was observed that tests performed on mortars and with a specific mix required an extended evaluation period to distinguish the behaviors. Furthermore, high early-strength cement featured the worst binder when faced with DEF.